A Note. Gir-profile of a Living Forest - Chavan, S. A. (Indian Forester, 1978)
The Gir forest of Gujarat covering nearly 1600 km2 -about â…” deciduous and the rest open tborny scrub-forest has been constituted into a wild life Sanctuary. This Article deals witb the complex food chain existing in this forest.